Axolotl mandible regeneration following complete transverse amputation involves a blastema formation and exhibits a limit along the proximodistal axis - Samanta Tarquino González; Belfran Carbonell-Medina (PLoS ONE, 2026)
Current therapeutic strategies aimed at promoting the regeneration of craniofacial tissues do not fully address all physiological and aesthetic needs. This highlights the need to investigate the regenerative response of craniofacial tissues in regenerative species like Ambystoma mexicanum ( A. mexicanum ), particularly concerning the mandible. However, although previous studies have demonstrated the regenerative response after lateral cuts of the mandible in A. mexicanum , it is unknown whether it can regenerate the mandible after complete transverse amputation, a type of injury used to remove tumors and extensive lesions that involve the symphyseal and parasymphyseal. Furthermore, it remains uncertain whether there is a limit to the regenerative response along the mandible proximal-distal axis. In light of this, we assessed the regenerative response following axolotl mandible complete transverse amputation through macroscopic and histological analyses and skeletogenic assessment via diaphanization. We also evaluated proliferation and the expression of genes associated with blastema formation. The results indicate that following mandibular injury, a blastema formed from which all amputated tissues were regenerated by 180 days post-amputation (dpa) and integrated seamlessly with the remaining structures. However, morphological alterations were noted in the regenerated skeletal elements. Additionally, we identified the expression of genes characteristic of epimorphic regeneration, including Prrx1, Kazald1, Msx2, Pax7 , and Sox2 . Interestingly, regenerative failure was observed after a second, more proximal amputation. Together, our findings suggest that the regenerative response to complete transverse amputation of the mandible in axolotls is fundamentally epimorphic; however, this regenerative capacity appears to have limits along the mandible proximal-distal axis.